Micropropagação e conservação in vitro de Orthophytum mucugense Wand. e Conceição - Lima, Andressa Priscila Piancó Santos (2016)
Chapada Diamantina – BA presents endemic especies with ornamental potential among which is Orthophytum mucugense, which occurs in the municipality Mucugê. This species is a target of extractivism and it is considered vulnerable, rendering studies of propagation and conservation of the species necessary. Therefore, the objective of this study was to establish protocols of micropropagation and in vitro conservation of O. mucugense. To that end, morphogenetic responses were evaluated in three types of explants, stem, root and leaf under the effect of different concentrations of the plant growth regulators NAA, 2,4-D and BAP. Sprouts formation in stem explants by direct organogenesis, in basal leaf explants by indirect organogenesis and callus formation in basal root and leaf explants were obtained. The rooting of the shoots was carried out with 1 coal g.L-1 activated for 30 days, and microplants acclimatized in a greenhouse with direct exposure to the environment. These results evince that tissue culture is a viable tool for in vitro propagation of O. mucugense. In in vitro conservation the effect of the medium salts reduction, of osmotic agents and of the retardant ancymidol in the minimum growth of the plants were tested; after 300 days of cultivation, analysis of the plant growth, of the chlorophyll content and of the regenerative capacity were carried out. On the basis of these assessments, the ancymidol, in the concentrations used, is not efficient in minimal growth induction, and the reduction of MS salts to ⅟3, with the combination of 45 g.L-1 of sucrose with 7.8 g.L-1 of mannitol is indicated for in vitro conservation of O. mucugense.